2008
DOI: 10.1136/jnnp.2007.133520
|View full text |Cite
|
Sign up to set email alerts
|

Bone-marrow transplantation fails to halt intrathecal lymphocyte activation in multiple sclerosis

Abstract: The persistence of CSF lymphocyte activation markers sCD27 and intrathecal oligoclonal IgG bands after maximum immunoablative treatment indicates that complete eradication of activated lymphocytes from the CNS has not been established. This is paralleled by disease progression observed in several studies on the effect of stem-cell transplantation in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Although this cross-sectional study does not provide evidence for the dynamic nature of the biomarkers studied, published longitudinal studies, either in the CSF or blood (in systemic inflammatory conditions) document their correlation with the severity of inflammatory processes and their responses to immunomodulatory treatments. 30,38 We confirmed the dynamic nature of these biomarkers in anecdotal observations during therapeutic management of some of the most difficult-to-treat OIND patients (data not shown), and plan to formally validate these biomarkers as pharmacodynamic markers in ongoing clinical trials (NCT01212094 and NCT01143441).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Although this cross-sectional study does not provide evidence for the dynamic nature of the biomarkers studied, published longitudinal studies, either in the CSF or blood (in systemic inflammatory conditions) document their correlation with the severity of inflammatory processes and their responses to immunomodulatory treatments. 30,38 We confirmed the dynamic nature of these biomarkers in anecdotal observations during therapeutic management of some of the most difficult-to-treat OIND patients (data not shown), and plan to formally validate these biomarkers as pharmacodynamic markers in ongoing clinical trials (NCT01212094 and NCT01143441).…”
Section: Discussionsupporting
confidence: 59%
“…Conversely, cell counts from unspun CSF are insensitive to mild to moderate levels of inflammation. 11 Although novel biomarkers of active intrathecal inflammation have been proposed, 2530 none of them has been implemented in clinical practice. 31 Several plausible reasons include a perceived or actual lack of experimental rigor; the absence of validation in blinded, prospectively acquired cohort(s); and sparse evidence that new biomarkers offer additional clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that levels of sCD27 and sCD30 decreased following chemotherapy, which induces an immunosuppressive status (22)(23)(24). The observed general reduction in blood levels of measured markers with increasing TCDD levels is consistent with the earlier observation among the same study subjects that indicated a general decrease in most cytokine-, chemokine-, and growth factors levels with increasing TCDD exposure levels (17) and provides more evidence that TCDD exposure could lead to a general suppression of the immune system.…”
Section: Discussionsupporting
confidence: 87%
“…sCD27 and sCD30 are reportedly important regulators of the Th1/Th2 balance in the immune response and they are considered markers of lymphocyte activation 28. Decreased release of sCD27 by activated B and T cells following chemotherapy and bone marrow transplantation has been reported, consistent with the immunosuppression associated with such regimens 29. While severe immunosuppression in several types of clinical situations is a definite aetiological factor for NHL, it remains to be clarified if milder immune alterations could be a mechanism of action for TCE-induced NHL in the occupational setting.…”
Section: Discussionmentioning
confidence: 90%